THE EFFECT OF USING SCREEN RECORDING APPLICATION AS A MEDIA TO TEACH ONLINE CLASSES - ade ari yuliastini (Lingua Scientia, 2021)
AbstractStudents from elementary and secondary education use computers or tablets to access online learning materials when their classrooms and colleges are closed due to a COVID-19 pandemic. This condition has caused a huge demand for students and teachers to use the screen recording application. However, the application for screen recording was a self-talking application that would be comparatively passive for student contact. Owing to the uninvolved results of more than listening, disengaged in class tasks and quickly disturbed, teachers needed to have general principles to construct their teaching in online classroom environments as a simple reference. The system of application, based on three methods are [u1] constructive learning, inspiration and feedback may be assumed to be involved, accountable and cognitive in promoting the response of students. Keywords : Screen Recording Application, Screen Recording Effects, Online Learning, Learning Method  [u1]In which dihapus à are